Analysis of People’s Attitudes towards Subsidized Rural Timber Allotment and Community Forestry in Sarpang Dzongkhag, Bhutan - Tempa, Karma; Jamroenprucksa, Monton (วารสารวนศาสตร์ไทย, 2022)
This research investigated people’s attitudes towards the subsidized rural timber allotment (SRTA) policy and the community forestry (CF) approach in Bhutan. It was assumed that there was no people’s participation under the current SRTA policy and this was a threat to sustainable forest management (SFM). Samples for the study consisted of rural households in Dekiling geog (block), a part of Sarpang Dzongkhag (district). Both quantitative and qualitative data were collected through household interviews. Statistical tests as well as the perceptions of different categories of people based on occupation, social status, education and age groups confirmed that there was little or no people’s participation in forest management under the current SRTA policy. The attitudes of people on SFM (c2= 14.514, p < 0.024) indicated uncertainty in the future supply of rural timber. The assessment of both the attitudes of people on SRTA and the opinions of people towards CF strongly favored replacing SRTA by CF to achieve sustainable forest management. Keywords: people’s attitudes, subsidized rural timber allotment, community forestry, Bhutan